PERANCANGAN SEMI ANECHOIC ROOM PADA LABORATORIUM GETARAN DAN AKUSTIK JURUSAN TEKNIK MESIN FAKULTAS TEKNIK UNIVERSITAS GADJAH MADA YOGYAKARTA (DESIGN OF A SEMI- ANECHOIC ROOM OF THE VIBRATION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
, 136-148, Prentice-Hall Inc., New Jersey. ABSTRACT The purpose of the design was to acquire a room which could absorb sufficiently sound occurring in it and to isolate sound coming from outside so that it did not get into the room. The semi-anechoic room was located within the Vibration and Acoustics Laboratory, Department of Mechanical Engineering, the Faculty of Engineering, Gadjah Mada University, occupying an area of 7.5 m x 5.4 m x 3.7 m. The outer wall of the room was made of plastered bricks, coated with glass wool absorber. The absober material was fixed on a wooden structure, 15 cm away from the wall, which was then covered with an acoustic wall. The analysis of the result of the semi anechoic room showed that room isolation was sufficiently good, having a back ground noise of 24 dB. The sound absorption in the room was also sufficiently good, having a reverberation time of 0.375 to 0.4 second, especially for the sound with frequencies of 125 Hz to 500 Hz, and no echoes was occurred when there was a sudden sound. Accordingly, the semi anechoic room can be used to measure sound characteristics and intensity, particularly that having a low frequency.